Knud Rasmussen Glacier Status Analysis Based on Historical Data and Moving Detection Using RPAS - Karel Pavelka; Jaroslav Šedina; Karel Pavelka (Applied Sciences, 2021)
This article discusses partial results of an international scientific expedition to Greenland that researched the geography, geodesy, botany, and glaciology of the area. The results here focus on the photogrammetrical results obtained with the eBee drone in the eastern part of Greenland at the front of the Knud Rasmussen Glacier and the use of archive image data for monitoring the condition of this glacier. In these short-term visits to the site, the possibility of using a drone is discussed and the results show not only the flow speed of the glacier but also the shape and structure from a height of up to 200 m. From two overflights near the glacier front at different times, it was possible to obtain the speed of the glacier flow and the distribution of velocities in the glacier stream. The technology uses a comparison of two point clouds derived from a set of aerial photos taken with the eBee drone, and calculating the M3C2 (Multiscale Model-to-Model Cloud Comparison) distances with CloudCompare software. The results correlate with other measurement methods like accurate and long-term measurement with Global Navigation Satellite System (GNSS), satellite radar, or ground geodetical technology. The resulting speed from the drone data reached in the middle part of the glacier, was approximately 12–15m per day. The second part of the paper focuses on the analysis of modern satellite images of the Knud Rasmussen Glacier from Google Earth (Landsat series 1984–2016) and Sentinel 2a, and a comparison with historical aerial images from 1932 to 1933. Historical images were processed photogrammetrically into a three-dimensional (3D) model. Finally, orthogonalized image data from three systems (drone photos, historical aerial photos, and satellite data) were compared in the ArcGIS software. This allows us to analyze glacier changes over time in the time span from 1932 to 2020, with the caveat that from 1933 to 1983 we did not have data at our disposal. The result shows that more significant changes in the area of this glacier occurred after 2011. The main aim of this article is to research the use of photogrammetric methods for monitoring the condition and parameters of glaciers based on non-traditional technology, such as drones or new processing of historical photos.